Advancing IPM in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
workshop was held in Barbados from 16-19 October, 1994, to initiate a Caribbean IPM network